Process modelling of organized screening programs breast cancer - Marques, Inês Terras (2020)
Marques, I. T., Santos, C., & Santos, V. (2020). Process modelling of organized screening programs breast cancer. European Journal of Public Health, 30(Supl. 5), V537-V537. https://doi.org/10.1093/eurpub/ckaa166.022